Sexual function is correlated with body image and partnership quality in female university students - Wallwiener, Stephanie; Rietschel, Marcella (The journal of sexual medicine, 2016)
Introduction - According to the World Health Organization definition, sexual health is more than mere physical sexual function; it also encompasses emotional, mental, and social well-being in relation to sexuality and is not merely the absence of dysfunction or disease. In line with this definition, various studies have reported that female sexual function is associated with partnership quality, body image, and body self-acceptance. - Aim - To investigate whether female sexual function is influenced by (i) body self-acceptance and (ii) partnership quality, as important factors in psychosocial well-being, and (iii) whether the effects of body self-acceptance are moderated by partnership quality. - Methods - In total, 2,685 female medical students no older than 35 years from Germany, Austria, and Switzerland completed an anonymous online questionnaire comprising the Female Sexual Function Index (FSFI) and the Self-Acceptance of the Body Scale. Respondents were asked to state whether they had been in a steady partnership in the preceding 6 months. When present, the quality of the partnership status was rated (enamoredness, love, friendship, or conflicted). To determine correlations, group differences, and moderating effects among body self-acceptance, partnership quality, and sexual function, the data were analyzed using Spearman correlations, Kruskal-Wallis tests, and analyses of variance. - Main Outcome Measures - Female sexual function (FSFI total score). - Results - (i) In sexually active women, higher FSFI scores were significantly associated with greater body self-acceptance and a steady partnership during the preceding 6 months. (ii) Total FSFI scores were highest in women who described their partnership as enamored (29.45) or loving (28.55). Lower scores were observed in single women (26.71) and in women who described their partnerships as friendship (25.76) or as emotionally conflicted (23.41). (iii) Total FSFI score was affected by an interaction between body self-acceptance and partnership quality. Body self- acceptance was positively associated with FSFI total scores, particularly in single women and women in emotionally conflicted partnerships. - Conclusion - Our findings suggest that in young women, body self-acceptance and partnership quality are positively associated with better sexual function, and that high body self-acceptance might buffer the negative impact on sexual function of partnership quality. The present data suggest that psychological interventions to improve the body image of younger women can positively affect sexual function and thereby improve sexual health.